PENERAPAN PEMBELAJARAN TAPPS (THINKING ALOUD PAIR PROBLEM SOLVING) UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA - ', Komariyah; Irianti, Mitri; ', Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This research aimed to describe and found out the enhancement of students cognitive learning outcomes through the implementation of TAPPS (Thinking Aloud Pair Problem Solving) learning on uniform circular motion physic matter in MA Negeri 1 Pekanbaru. As the research method, it used Quasi Eksperimental Design, and it’s research design was Intact Group Comparisson. It’s samples were two classes, those consisted of 29 students as the experimental class and 30 students as the control class. The data collection instrument was posttest questions consisted of 23 multiple choice questions objectively. The data analysis technique that used was descriptive analysis by comparing the students absorption ability and inferential analysis by looking at the difference of learning outcomes between two these classes. The results of this research showed that there were differences of learning outcomes between the experimental and control class which students absorption ability of the experimental were 5.74 percents higher than the control class. Therefore, it can be concluded that implementation of TAPPS (Thinking Aloud Pair Problem Solving) learning was effective to enhanced students cognitive learning outcomes on phisic matter. Keyword: TAPPS (Thinking Aloud Pair Problem Solving) Learning, Cognitive Learning Outcomes.